Skrining Fitokimia Dan Analisis Kuantitatif Ekstrak Daun Randu (Ceiba pentandra (L.) Gaertn.) Dengan HPLC Dan Uji Aktivitas Antibakteri Terhadap Pertumbuhan Bakteri P. aeruginosa ATCC 27853 - Salsabila, Luqyana; Putri, Amalia Eka (Jurnal Farmasi & Sains Indonesia, 2023)
Nosocomial pneumonia or commonly known as hospital acquired pneumonia (HAP) is an infection that occurs in the lung parenchyma caused by pathogens in the hospital. Nosocomial pneumonia is the 6th leading cause of death in Indonesian hospitals with a mortality rate of 20-50%. Nosocomial pneumonia is caused by pathogenic microorganisms such as the gram-negative bacterium Pseduomonas aeruginosa ATCC 27853. One of the plants that has the potential as an antibacterial is the randu plant (Ceiba pentandra (L.) Gaertn.) because it contains compounds such as alkaloids, flavonoids, saponins and tannins. The purpose of this study was to determine the levels of quercetin compounds contained from randu plants using HPLC and to determine the antibacterial activity of randu plants against Pseduomonas aeruginosa ATCC 27853 by looking at the size of the inhibition zone formed. The method used is the disc diffusion method. The results of this study indicate that the randu leaf extract contains the compound quercetin which is included in the class of flavonoid compounds with a concentration of 2.075%. 5%. The results of testing the antibacterial activity of randu leaf extract against Pseduomonas aeruginosa ATCC 27853 in the negative control did not form an inhibition zone, the positive control produced an inhibition zone of 29.7 mm, at a concentration of 15%, 25% and 35% produced an inhibition zone of 13.3 mm, 14.6mm and 15.6mm. optimal antibacterial activity is found at a concentration of 15%.